Global stability of delayed Hopfield neural networks under dynamical thresholds - Fei-Yu Zhang; Wan-Tong Li (Discrete Dynamics in Nature and Society)
We study dynamical behavior of a class of cellular neural networks system with distributed delays under dynamical thresholds. By using topological degree theory and Lyapunov functions, some new criteria ensuring the existence, uniqueness, global asymptotic stability, and global exponential stability of equilibrium point are derived. In particular, our criteria generalize and improve some known results in the literature.